HUBUNGAN KEPATUHAN MENGKONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA KEHAMILAN - Sukmawati; Lilis Mamuroh; Furkon Nurhakim (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The incidence of anemia in pregnant women remains high in Indonesia. The incidence of anemia in pregnant women in Garut Regency in 2017 (24,52%) has decreased lower than the National incidence rate however but still above the National target. Anemia conditions can increase a variety of risks when pregnant women, give bitrh and the fetus. The risks is haemoragic post partum, the mother is susceptible infection and abortion. Anemia increases the risk of bleeding in mothers during labour and it is one of the causes of death. One of the factors affecting anemia in pregnant women is the compliance on Fe consumption. This study aims to analyze the correlation between the compliance on Fe tablet consumption and anemia during pregnancy. The study was a correlational study and utilized cross sectional design. The study, conducted at Haurpanggung Community Health Center, Garut Regency, took 70 pregnant women as the sample and they were selected using simple random sampling. The data were collected through the questionnaire examining the pregnant women’s compliance in consuming Fe tablets. The data were analyzed using univariate and bivariate analysis. The results showed that most pregnant women were not compliant in consuming Fe tablets and there was a correlation between the compliance of Fe tablet consumption and anemia during pregnancy. Health education about the importance of consuming Fe tablets properly and correctly is expected to motivate the mother in consuming Fe tablet.